Development of Mobile Learning Application for Chinese Pinyin with Virtual Assistant - Hai, Yen Nee; Wahid, Noorhaniza (Applied Information Technology And Computer Science, 2023)
Hanyu Pinyin is the official romanization of the Mandarin Chinese language. It helps both native and non-native Chinese speakers to learn and understand the Mandarin language. The existing Google Play applications for learning Hanyu Pinyin lack of multimedia elements such as graphics and animations and have yet to be implemented with a virtual assistant such as speech recognition. Therefore, this project is proposed to develop a mobile learning application namely Learn PINYIN that helps the beginner to learn Pinyin. The target users for this project are children aged 7 to 12. Multimedia Mobile Content Development (MMCD) approach is used to develop the Learn PINYIN application. According to user acceptance testing, positive results were obtained with an average of 37.22% of respondents agreeing and 38.70% strongly agreeing with the statements. This application is expected to assist the learners to learn the fundamental of Pinyin, and the addition of a game module and a practice module for speech recognition are suggestions for future work on this project.